Potensi Geo-Homestay Kabupaten Jeneponto Sebagai Preferensi Destinasi Tujuan Wisatawan Jepang - Anda Prasetyo Ery; Masri Ridwan; Handoko Handoko (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2022)
This study aims to determine the Tourism Potential through Mapping the Geohomestay Potential of Japanese tourist preferences as an innovation in the new normal period in Jeneponto Regency, South Sulawesi as an Innovation in the Covid-19 Pandemic Period. The approach taken is descriptive qualitative with data collection methods through interviews and tourist attraction surveys. Data analysis by triangulation on key informants. Informants include the head of the destination, tourist village managers, village heads and the community in Jeneponto Regency. Meanwhile, to determine the location of geo-homestays, it is done by overlaying data consisting of the distribution of tourist villages, natural, cultural and historical potential using the Arcgis 10.5 mapping application. The conclusions of this study include the tourist attractions of Jeneponto Regency including beaches, caves, seas, islands, panoramas, agro, traditional-cultural history and industrial tourism. The Tourism component of Jeneponto Regency includes Attractions, Amenities, Accommodations and Accessibility. The development of geo-homestays in Jenoponto Regency follows the natural potential of the surroundings spread over 11 (eleven) villages/kelurahan, including: Je'ne Tallasa Village, Rumbia Village, Tompo Bulu Village, Ujung Bulu Village, Paitana Village, Je'ne Tallasa Village, Tonro Kassi Barat, Arungkeke Village, Ex. Pabiringa, Tarowang Village and Kampala Village. This study recommends the community, actors, and the government to package promotional products and homestay branding based on the existing geographic potential in accordance with the preferences of Japanese tourists.